Method for preparing cement by using aluminum electrolysis cell overhaul slag and cement

By mixing overhaul slag with other raw materials and controlling specific proportions and temperatures, high-performance cement can be prepared, solving the problems of harmless treatment and resource utilization of overhaul slag in cement production, and realizing efficient and environmentally friendly cement production.

CN120987582APending Publication Date: 2025-11-21EAST CHINA UNIV OF SCI & TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511035640.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In the current technology, the harmless treatment and resource utilization of aluminum electrolytic cell overhaul slag have not yet been integrated, and its application in cement production has not been fully studied.

Method used

Cement clinker is prepared by mixing overhaul slag with raw materials such as limestone, clay, iron powder, and sandstone, controlling specific proportions and temperatures, and then adding gypsum and fly ash to optimize the composition ratio, thus forming high-performance cement.

Benefits of technology

It has achieved the harmless treatment and resource utilization of overhaul slag, reduced energy consumption, reduced carbon emissions, and produced high-strength cement that meets standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for preparing cement from overhaul slag of an aluminum electrolysis cell. The method comprises the following steps: proportioning raw materials: 20-80% of limestone, 1-25% of clay, 1-10% of iron powder, 1-5% of sandstone and 1-50% of overhaul slag powder; the saturation coefficient of the lime is 0.88-0.92, the silicic acid rate is 2.3-2.7, and the aluminum oxygen rate is 1.5-1.8; after uniformly mixing, adding 1-10wt% of water, fully mixing, and heating and drying the powder to constant weight; putting the raw material into a heating device, heating from room temperature to 1000-1800 DEG C, keeping the temperature constant, quickly taking out after firing, and quenching to obtain clinker; sealing and storing in a dry container; and crushing the cooled clinker by a crusher, homogenizing the crushed clinker in a clinker warehouse, and uniformly mixing and grinding the obtained clinker, gypsum, the overhaul slag and fly ash to obtain the cement prepared from the overhaul slag. The invention also discloses the cement prepared by the method. Silicon, aluminum, iron and calcium oxides in the overhaul slag serve as metal elements to supplement and replace slag, hazardous solid waste is subjected to innocent treatment, resource utilization is achieved at the same time, economical efficiency is better, practicability is higher, and the application prospect is wider.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of harmless treatment of solid waste from the aluminum electrolysis industry, specifically to a method for harmlessly treating overhaul slag and using the overhaul slag as a raw material in cement preparation. Background Technology

[0002] Aluminum is widely distributed in nature, ranking third in abundance in the Earth's crust after oxygen and silicon, making it the most abundant metallic element in the Earth's crust. Aluminum's position in the periodic table, after sodium and magnesium, determines its relatively reactive chemical properties, thus it exists in nature as oxides and silicates. Long ago, humans used clay containing aluminum compounds to make utensils for their use.

[0003] Aluminum is currently the most demanded non-ferrous metal in the world. It possesses excellent thermal and electrical conductivity, corrosion resistance, and is relatively lightweight, making it widely used in various fields such as transportation, electrical industries, and aerospace. With the improvement of my country's primary aluminum production level and further development of aluminum properties, the aluminum industry's development prospects will be even broader.

[0004] Currently, large-scale industrial production of aluminum almost exclusively employs the cryolite-alumina molten salt electrolysis method. The basic principle of this method is as follows: carbon materials are used as the anode of the aluminum electrolysis cell, molten aluminum as the cathode, metallurgical-grade alumina as the electrolytic raw material, and cryolite melt as the electrolyte solution. Electrolysis is carried out under direct current conditions. A reduction reaction occurs at the cathode to produce molten aluminum, while an oxidation reaction occurs at the anode to release carbon monoxide and carbon dioxide gases. The overall electrolysis reaction process is shown below.

[0005] Al₂O₃ (molten) + 1.5C (s) → 2Al (l) + 1.5CO₂ (g)

[0006] The electrode reaction process is as follows:

[0007]

[0008] Cathode reaction:

[0009] Al 3+ (络合态) +3e - →Al(l)

[0010] Anode reaction:

[0011] O 2- (络合态) -2e - →O (原子)

[0012] 2O (原子) +C (原子) →CO2(g)

[0013] High concentrations of soluble fluorides and cyanides were found in the slag from aluminum electrolytic cells overhaul, including F. - and CN - The contents were approximately 2000 mg / L and 15 mg / L, respectively, of which F - The concentration of fluoride can reach as high as 6000 mg / L. The fluoride concentration exceeds the maximum limit of 100 mg / L for fluoride concentration in leachate specified in the "Standard for Identification of Hazardous Waste—Leaching Toxicity Identification" (GB5085.3-2007). Therefore, in June 2016, various wastes from the aluminum electrolysis process, including maintenance slag, were included in China's "National Hazardous Waste List," with waste code 321-023-48 and a hazardous characteristic of "T" (leaching toxicity). The state has issued relevant policies prohibiting the open-air storage, illegal discharge, and transfer of aluminum electrolysis maintenance slag.

[0014] During the overhaul of aluminum electrolytic cells, the dismantled waste cell linings contain large amounts of fluorides and cyanides. If not properly handled, the fluorides in the overhaul slag will gradually dissolve under the scouring action of rainwater, resulting in F... - In its incubation period, cyanide seeps into the soil, polluting not only the topsoil but also penetrating deeper layers through rainfall and irrigation, disrupting the soil's ecosystem. A small portion of the cyanide in SPL may decompose at temperatures above 250°C, and almost all of it can be decomposed at 800-1100°C. Since the late 1980s, many countries worldwide have classified aluminum electrolysis overhaul slag as hazardous waste, prohibiting open-air storage and requiring safe landfill or harmless treatment.

[0015] Overhaul slag can be categorized into cathode carbon block waste slag, cathode paste waste slag, anti-seepage material waste slag, refractory brick waste slag, castable waste slag, and calcium silicate board waste slag, etc. However, some existing technologies for the harmless treatment of overhaul slag are targeted at specific wastes. For example, CN114751666A focuses on treating waste aluminum electrolysis cathode carbon blocks, using coarse-grained particles as aggregate to produce magnesium sulfate-oxygenated cement material containing waste cathode carbon blocks. Specifically, it utilizes the aluminum and silicon content in the waste cathode carbon blocks as aggregate, and adds magnesium to prepare a novel magnesium sulfate-type cementitious material. Alternatively, it emphasizes the utilization of the carbonaceous components. CN113480204A utilizes the carbonaceous components of overhaul slag to co-fire coal for thermal power generation, where fluorides are absorbed by calcium, and the aluminum and silicon components are used as raw materials for cement production. CN118851223A discloses a method for co-utilizing fly ash and overhaul slag to recover carbonaceous components, primarily focusing on carbon recovery.

[0016] Currently, there is still a pressing need to study methods for the integrated application of overhaul slag separation in cement production. Summary of the Invention

[0017] Therefore, the technical problem to be solved by the present invention is to provide a method for preparing cement using the overhaul slag of aluminum electrolysis cells.

[0018] The technical solution of the present invention is a method for preparing cement using slag from an aluminum electrolysis cell overhaul, comprising the following steps:

[0019] (1) Grind the raw materials into powder and mix them according to the following mass ratio: 20-80% limestone, 1-25% clay, 1-10% iron powder, 1-5% sandstone, and finally add 1-50% of the total mass of overhaul slag powder; the raw material ratio is controlled so that the lime saturation coefficient (KH) is 0.88-0.92, the silica content (SM) is 2.3-2.7, and the alumina content (IM) is 1.5-1.8;

[0020] After uniform mixing, add 1-10 wt.% water and mix thoroughly, then heat and dry the powder to constant weight; to obtain the raw meal of overhaul slag mixture;

[0021] (2) Place the raw material into the heating device and raise it from room temperature to 1000-1800℃. After reaching the set temperature, keep it at the temperature for 30-60 minutes. After the firing is completed, take it out quickly and cool it rapidly to obtain the clinker. Then seal and store it in a dry container.

[0022] (3) After the cooled clinker is crushed by the crusher, it enters the clinker silo for homogenization to ensure the stability of chemical composition. Then, the obtained clinker, gypsum, overhaul slag and fly ash are mixed. The gypsum addition ratio is 1-10% of the clinker weight, and the overhaul slag and fly ash mixing ratio is 1-30%. After grinding evenly, it becomes the final cement prepared from the overhaul slag.

[0023] The lime saturation coefficient (KH) is 0.88-0.92, the silicate ratio (SM) is 2.3-2.7, and the alumina ratio (IM) is 1.5-1.8, etc. These coefficients are used to measure the performance of cement and are mainly determined by its composition. By controlling the composition ratio within this range, the subsequent strength and the initial and final setting times can be guaranteed.

[0024] In this invention, the overhaul residue is processed twice: once in the preparation of raw meal into clinker, and again in the mixing of clinker, gypsum, and overhaul residue. This operation aims to fully utilize all components of the overhaul residue. In step (1) of raw meal preparation, the overhaul residue provides aluminosilicates, which can replace part of the cement powder. Furthermore, the carbon and fluorine elements in the overhaul residue can replace part of the traditional coal powder in clinker preparation, reducing energy consumption. Step (3) mainly utilizes carbon and aluminosilicates, similar to the role of adding slag or fly ash to clinker.

[0025] After completing step (2), the above process will yield clinker prepared from overhaul slag. The clinker will be ground by grinding equipment, and the resulting powder will be tested for quality, which will then be the final cement prepared from the overhaul slag.

[0026] In step (3), the overhaul slag in this process provides slag and carbon elements, which can reduce energy consumption, improve performance, and reduce carbon emissions.

[0027] According to a method for preparing cement using aluminum electrolytic cell overhaul slag according to the present invention, preferably, the overhaul slag is derived from overhaul slag raw material generated in the electrolytic aluminum industrial project.

[0028] Preferably, the mixing ratio in step (1) is: 25-70% limestone, 1-20% clay, 1-10% iron powder, 1-5% sandstone, and 1-40% overhaul slag powder.

[0029] According to a method for preparing cement using aluminum electrolysis cell overhaul slag according to the present invention, preferably, the grinding in step (1) is grinding to particles smaller than 0.25 mm.

[0030] According to a method for preparing cement using aluminum electrolytic cell overhaul slag, it is preferred that the heating rate from room temperature to 1000-1800℃ in step (2) is 10-30℃ / min.

[0031] According to a method for preparing cement using aluminum electrolysis cell overhaul slag of the present invention, preferably, the quenching in step (2) refers to a cooling rate of 100-800℃ / minute. Quenching is to rapidly cool the produced clinker to ensure its stable composition, good cement performance, and convenient subsequent processing. Quenching of cement clinker is generally carried out in a clinker cooler. Currently, the industrial cooling rate range is 100-800℃ / minute. The initial cooling rate needs to be fast (able to quickly reduce the temperature from 1300℃ to 600-800℃), and the cooling rate can be slowly reduced after stabilization.

[0032] According to a method for preparing cement using aluminum electrolytic cell overhaul slag according to the present invention, preferably, in step (2), the temperature is raised from room temperature to 1100-1700℃.

[0033] According to a method for preparing cement using aluminum electrolytic cell overhaul slag according to the present invention, preferably, the clinker bin homogenization in step (3) takes between 3 and 12 hours.

[0034] The clinker is then homogenized in the clinker silo for 3-12 hours to ensure minimal deviation in clinker composition. Storage should be at room temperature, controlled between 10-30℃ to prevent clinker clumping or moisture absorption; relative humidity should be maintained below 60% to prevent clinker pulverization. Good air circulation should be maintained to prevent moisture accumulation, and the clinker should be kept away from heat sources. A slight positive pressure (5-10 Pa) can be maintained in the clinker silo to prevent external moisture from entering. There are no specific requirements for the clinker addition ratio; gypsum and overhaul residue should be added in appropriate proportions based on the quality of the clinker.

[0035] According to a method for preparing cement using aluminum electrolytic cell overhaul slag according to the present invention, preferably, the overhaul slag and fly ash mixture in step (3) accounts for 10-40% of the clinker mix.

[0036] The present invention also provides a method for preparing cement using aluminum electrolysis cell overhaul slag, wherein the cement has a 28-day compressive strength ≥42.5MPa, a setting time of initial setting ≥45 minutes, and a final setting time of less than or equal to 10 hours.

[0037] The beneficial effects of this invention are as follows:

[0038] This invention utilizes the carbon in overhaul slag to replace fuel resources in clinker production and processing. The fluorides in the slag, due to their catalytic and mineralizing effects, can also be used as fluxing agents or mineralizing agents to lower the required reaction temperature and reduce the amount of coal needed. The silicon, aluminum, iron, and calcium oxides in the overhaul slag can supplement the metal elements in raw starch and replace slag, achieving resource utilization while harmlessly treating hazardous solid waste. This approach is more economical, practical, and has broader application prospects. Attached Figure Description

[0039] Figure 1 A process for preparing cement using overhaul slag as raw material. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0041] Example 1

[0042] A schematic diagram illustrating the process of preparing cement using aluminum electrolysis cell overhaul slag as raw material according to this invention is shown below. Figure 1 As shown.

[0043] 1) Weigh 80.00g of ground limestone powder, 10.00g of clay powder, 5.00g of iron powder, 5.00g of sandstone powder, and 10.00g of overhaul slag powder. Mix them evenly and then add 10.00ml of deionized water and mix thoroughly to obtain raw material cake.

[0044] 2) Place the raw material into a high-temperature heating furnace and heat it from room temperature to 1300℃ at a rate of 20℃ / min. After reaching the set temperature, keep it at the set temperature for 60 minutes. After the firing is completed, take it out quickly and cool it to 60℃ to obtain the clinker. Pack it into a sealed bag and store it in a desiccator.

[0045] 3) Weigh 60g of clinker powder, 5g of gypsum, and 35g of overhaul slag powder, grind and mix them to obtain overhaul slag cement product.

[0046] 4) The prepared overhaul slag cement product underwent elemental and physical testing, and the results are shown in the table below. It conforms to the Chinese national cement standard (GB175-2023).

[0047] Table 1 Chemical composition of raw and cooked food in application examples.

[0048] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO KH SM IM raw materials 54.36 0.42 1.21 44.01 0.90 2.40 1.78 Cooked 29.08 0.83 1.32 68.77 0.88 2.38 1.54

[0049] Table 2 Physical properties of clinker

[0050]

[0051]

[0052] Example 2

[0053] A schematic diagram illustrating the process of preparing cement using aluminum electrolysis cell overhaul slag as raw material according to this invention is shown below. Figure 1 As shown.

[0054] 1) Weigh 80.00g of ground limestone powder, 10.00g of clay powder, 5.00g of iron powder, 5.00g of sandstone powder, and 5.00g of overhaul slag powder. Mix them evenly and then add 10.00ml of deionized water and mix thoroughly to obtain raw material cake.

[0055] 2) Place the raw material into a high-temperature heating furnace and heat it from room temperature to 1300℃ at a rate of 30℃ / min. After reaching the set temperature, keep it at the set temperature for 60 minutes. After the firing is completed, take it out quickly and cool it to 60℃ to obtain the clinker. Pack it into a sealed bag and store it in a desiccator.

[0056] 3) Weigh 100g of clinker powder, 5g of gypsum, and 5g of overhaul slag powder, grind and mix them to obtain overhaul slag cement product.

[0057] 4) The prepared overhaul slag cement product underwent elemental and physical testing, and the results are shown in the table below. It conforms to the Chinese national cement standard (GB175-2023).

[0058] Table 3 Chemical composition of raw and cooked food in Application Example 2

[0059] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO KH SM IM raw materials 13.2 3.5 3.0 44.5 0.91 2.15 1.17 C3S C2S C3A C4AF KH SM IM Cooked 58.2 18.0 7.9 9.1 0.92 2.12 1.15

[0060] Table 4 Physical Properties of Clinker

[0061]

[0062]

[0063] Example 3

[0064] A schematic diagram illustrating the process of preparing cement using aluminum electrolysis cell overhaul slag as raw material according to this invention is shown below. Figure 1 As shown.

[0065] 1) Weigh 61.00g of ground limestone powder, 10.00g of clay powder, 2.80g of iron powder, 6.20g of sandstone powder, and 20.00g of overhaul slag powder. Mix them evenly and then add 10.00ml of deionized water and mix thoroughly to obtain raw material cake.

[0066] 2) Place the raw material into a high-temperature heating furnace and heat it from room temperature to 1500℃ at a rate of 20℃ / min. After reaching the set temperature, keep it at the set temperature for 60 minutes. After the firing is completed, take it out quickly and cool it to 60℃ to obtain the clinker. Pack it into a sealed bag and store it in a desiccator.

[0067] 3) Weigh 100g of the prepared clinker powder, add 5g of gypsum and 5g of overhaul slag powder, grind and mix to obtain the overhaul slag cement product.

[0068] 4) The prepared overhaul slag cement product underwent elemental and physical testing, and the results are shown in the table below. It conforms to the Chinese national cement standard (GB175-2023).

[0069] Table 5 Chemical composition of raw and cooked food in Application Example 3

[0070] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO KH SM IM raw materials 14.12 2.65 3.18 41.86 0.90 2.40 0.88 Cooked 22.11 4.15 4.98 65.48 0.90 2.52 0.83

[0071] Table 6 Physical Properties of Clinker

[0072]

[0073] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing cement using slag from an aluminum electrolysis cell overhaul, characterized in that: Includes the following steps: (1) Grind the raw materials into powder and mix them according to the following mass ratio: 20-80% limestone, 1-25% clay, 1-10% iron powder, 1-5% sandstone, and finally add 1-50% of the total mass of overhaul slag powder; the raw material ratio is controlled so that the lime saturation coefficient (KH) is 0.88-0.92, the silica content (SM) is 2.3-2.7, and the alumina content (IM) is 1.5-1.8; After uniform mixing, add 1-10 wt.% water and mix thoroughly, then heat and dry the powder to constant weight; to obtain the raw meal of overhaul slag mixture; (2) Place the raw material into the heating device and raise it from room temperature to 1000-1800℃. After reaching the set temperature, keep it at the temperature for 30-60 minutes. After the firing is completed, take it out quickly and cool it rapidly to obtain the clinker. Then seal and store it in a dry container. (3) After the cooled clinker is crushed by the crusher, it enters the clinker silo for homogenization to ensure the stability of chemical composition. Then, the obtained clinker, gypsum, overhaul slag and fly ash are mixed. The gypsum addition ratio is 1-10% of the clinker weight, and the overhaul slag and fly ash mixing ratio is 1-30%. After grinding evenly, it becomes the final cement prepared from the overhaul slag.

2. The method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: The overhaul slag is derived from the overhaul slag raw material generated in the electrolytic aluminum industrial engineering.

3. The method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: The mixing ratio described in step (1) is: 25-70% limestone, 1-20% clay, 1-10% iron powder, 1-5% sandstone, and 1-40% overhaul slag powder.

4. The method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: The grinding in step (1) is grinding to particles smaller than 0.25 mm.

5. A method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: The heating rate from room temperature to 1000-1800℃ described in step (2) is 10-30℃ / min.

6. A method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: The rapid cooling mentioned in step (2) refers to a cooling rate of 100-800℃ / minute.

7. A method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: In step (2), the temperature is raised from room temperature to 1100-1700℃.

8. A method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: The homogenization of clinker in step (3) takes between 3 and 12 hours.

9. A method for preparing cement using aluminum electrolysis cell overhaul slag according to claim 1, characterized in that: In step (3), the overhaul slag and fly ash mixture accounts for 10-40% of the clinker mix.

10. The cement prepared by the method for preparing cement using aluminum electrolysis cell overhaul slag as described in claim 1, characterized in that: The cement has a 28-day compressive strength ≥ 42.5 MPa, and a setting time of initial setting ≥ 45 minutes and final setting ≤ 10 hours.

Citation Information

Patent Citations

  • Method for preparing magnesium material by taking waste cathode carbon block in waste aluminum electrolysis as raw material

    CN114751666A

  • Resourceful treatment method for electrolytic aluminum overhaul slag

    CN118851223A